Chapter Doctorates and Employability: New Perspectives for Doctoral Education - Lisimberti, Cristina (Studies on Adult Learning and Education, 2018)
Profound processes of change are affecting doctorates all over the world, above all, to provide broader employment prospects. However, the link between the transformations of a doctorate and employability is complex, and entails re-thinking formative pathways for doctorates by focusing on the professional identity of a PhD